The Effect of Public Service Obligation (PSO) Fare Subsidy Policy on The Quality of Service of Transjakarta Bus Rapid Transit (BRT) Services - Abidin, Zaenal; Yusuf, Maulana (Future Science, 2025)
This study aims to analyze the effect of the Public Service Obligation (PSO) tariff subsidy policy on the quality of TransJakarta Bus Rapid Transit (BRT) services. The focus is to measure how much the PSO tariff subsidy contributes to service quality improvement. A quantitative associative approach is used, with Thomas R. Dye’s (1981) theory of policy impact as the analytical framework, and the SERVQUAL model by Parasuraman et al. (1990) for measuring service quality dimensions. The sampling technique applied is purposive sampling with proportional distribution across 14 main TransJakarta BRT corridors, totaling 205 respondents. Data were collected via questionnaires and analyzed using simple linear regression. Findings reveal that the PSO tariff subsidy policy has a positive and significant partial effect on service quality, demonstrated by the rejection of the null hypothesis (H₀), and a coefficient of determination (R²) of 31.1%. This suggests that while subsidies play a crucial role in supporting fare affordability and closing operational gaps, 68.9% of service quality is influenced by other factors. The study highlights that financial support through subsidies is essential but not sufficient to ensure overall service quality. Non-financial factors such as passenger comfort, reliability, and trust also need attention. The DKI Jakarta Provincial Government is encouraged to maintain a sustainable and transparent PSO subsidy scheme. Meanwhile, PT TransJakarta should strengthen synergy with the Transportation Agency and diversify funding through non-farebox revenue to achieve a comprehensive and sustainable improvement in public transport services.